Plasmachemical technologies in biology and medicine: state of the art - T. M. Vasilieva (Тонкие химические технологии, 2015)
Low-temperature non-equilibrium plasmas have been extensively investigated due to their low-temperature properties and controllability of various agents such as radicals, ions, UV and electric fields, making them suitable for a wide range of biomedical applications. This paper presents an overview of the current status and potential of plasmachemical technologies for production of novel bioactive materials, fictionalization of organic polymers, deposition of organic and inorganic coatings, and plasma processing of biomaterials, sterilization, treatment of mammalian and cancerous cells, blood coagulation, wound healing and dental treatments. The brief summary and characterization of various low-temperature nonequilibrium plasmas used in biology and medicine (corona discharge, radio-frequency and microwave gas discharges, electron-beam plasma) are given. The physical-chemical processes of plasmachemical polymers modification and coatings synthesis, as well as mechanisms responsible for the biological effects are described.